Ciclagem de nutrientes e supressão de ervas espontâneas por adubos verdes sob um sistema em aléias - Freitas, Idelfonso Colares (2008)
The objective of this work was developed to evaluate the green manures of covering in the cycling of nutrients and suppression of weed in a system in alley crop with Clitoria fairchildiana R. A. Howard., It was used as reference in the culture of the maize in succession to the green manures for two years. The experiment was accomplished between May/2006 and May/2008 in an area of establish INCRA (Instituto National as of Colonisation and Reform Agraria), where is located on the 3º 36'S and 45º 24'W in the municipal district of Miranda do Norte-MA. The experimental outline has been used the blocks randomly with five treatments and four repetitions. Each of these sub parcels had 26m² and they were composed of the following species: T1-Stylosanthis capitata, T2-Crotalaria spectabilis, T3-Crotalaria juncea, T4-Canavalia ensiformes and T5-Control, trey were cultivated in two different systems: The first yearwithout cutting of the Clitoria fairchildiana for occasion of the and consortium of planting of the green manures. The second year-with cutting of the Clitoria fairchildiana the green manures among with caupi bean. The results just showed that the System with Stylosanthis capitata in the second year was not capable to supply the maize integrally with N to yield of 2.000 kg ha-¹, and all of the systems would be necessary complementation of P. The best yield of the maize for the first year was over on residues of the crotalarias and in the second year not has difference between the treatments. The best productivity of the caupi bean was among with Canavalia ensiformes with similar yield to the control; any system was capable to suppress the weed significantly in the studed conditions.